The challenges of implementing gold dinar in Kelantan: An empirical analysis - Yusuf, Muhammad-Bashir; Mat Ghani, Gairuzazmi; Meera, Ahamed Kameel Mydin (University of Malaya, 2013)

(untitled)
The purpose of this paper is to analyse the challenges of adopting the gold dinar as a currency in Kelantan, Malaysia. This is one of the earliest works to empirically investigate the challenges of using gold dinar currency since its introduction in Kelantan in August, 2010. The paper looks at both the internal and external challenges to the adoption of the new currency. The researchers came up with a model and a survey to validate the model. Structural equation modelling technique was employed to test if the data collected fits the model. It was found out that while the effects of both external and internal challenges were not statistically significant, they are significant in practical terms. All our measurement items were also found to be practical. Though the findings of the study indicate the challenges are not statistically significant, they nevertheless must be addressed if gold dinar is to be adopted in the future.